Use of a Journal Club During Level II Fieldwork to Facilitate Confidence and Skills for Evidence-Based Practice - Kelly A. Lavin (Scholarworks @ WMU, 2018)
Level II fieldwork students should have an opportunity to engage in the process of evidence-based practice (EBP) firsthand; however, ensuring that EBP is visible to students is often a challenge for fieldwork educators. This study investigated if the use of a journal club during a Level II, psychosocial fieldwork placement would increase the students' confidence and perceived abilities in using skills required for EBP. A descriptive study via survey design was used for the study. The participants consisted of two cohorts (n = 10) of occupational therapy graduate students. The results indicate that the students perceived an increase in their ability to search the literature and to comprehend and appraise research studies. These competencies appear to match the component skills associated with an ability to use evidence in practice. This study provides the method to develop a journal club during fieldwork to facilitate EBP skills for occupational therapy students.